The effect of the high environmental temperature on some blood parameters and the laying performance of Japanese quails with different body weights (short communication) - Ozcelik, M; Ozbey, O (Archiv Fur Tierzucht, 2004)
In this study, it was aimed to determine the effects of the high environmental temperature on blood parameters, egg productivity, egg weight and the eggshell thickness of the Japanese quails with different body weights. By this purpose, two temperature groups consisting of control (18-24degreesC) and experiment (35degreesC) groups and two weight groups as being heavy group (live weight >27 g) and light group (live weight <27 g) were constituted. At the end of the research, the effect of high temperature on some blood parameters were found as important statistically. The value of the egg productivity, egg weight and eggshell thickness were found lower at 35 C degree than the ones at 18-24 C degree in both weight groups.
Keywords: blood parameters; egg features; temperature; quail